Poetyka naturalistyczna w literaturze fantasy na przykładzie „Pieśni Lodu i Ognia” George’a R.R. Martina - Joanna Płoszaj (Literatura i Kultura Popularna)
The main goal of this article is to show and characterise elements of naturalist poetics in George R.R. Martin’s A Song of Ice and Fire fantasy series. Martin’s literary style is often referred to as ‘gritty realism’ because of the brutality inherent to the world it describes, which seems particularly hostile and unwelcoming towards the characters that inhabit it. But Martin’s novels seem also share a fair share of similarities with novels of the naturalist movement.